Commiphora benguelensis (Burseraceae), a new species from Angola - Swanepoel, Wessel (Phytotaxa, 2015)
Commiphora benguelensis Swanepoel, described here as a new species, is known only from the Kaokoveld Centre of Endemism, southwestern Angola. It appears to be closely related to C. africana. Diagnostic morphological characters of C. benguelensis include the white, glutinous exudate, smooth bark and hairy, trifoliolate leaves. Illustrations of the plant and a distribution map are provided. Mainly confined to near the coast, the new species is widespread but uncommon between Namibe and Santa Maria.